2016
DOI: 10.1016/j.neuron.2015.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Specific Striatal Substrates for Habitual Behavior

Abstract: The dorsolateral striatum (DLS) is implicated in habit formation. However, the DLS circuit mechanisms underlying habit remain unclear. A key role for DLS is to transform sensorimotor cortical input into firing of output neurons that project to the mutually antagonistic direct and indirect basal ganglia pathways. Here we examine whether habit alters this input-output function. By imaging cortically-evoked firing in large populations of pathway-defined striatal projection neurons (SPNs), we identify features tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(164 citation statements)
references
References 39 publications
(53 reference statements)
9
151
1
Order By: Relevance
“…The DLS is innervated by glutamatergic afferents from sensorimotor cortical areas (Hintiryan et al, 2016; McGeorge and Faull, 1989; Pennartz et al, 2009). The experience-dependent increase in MSN activity which was observed here, and in other studies (Barnes et al, 2005; Jin and Costa, 2010; Jog et al, 1999; Kimchi et al, 2009; Miyachi et al, 2002; Thorn et al, 2010; Yin et al, 2009), is consistent with an enhancement of corticostriatal coupling that accompanies some forms of learning (Koralek et al, 2013; O’Hare et al, 2016; Xiong et al, 2015). Thus, our results suggest that PV interneurons regulate MSN firing rate by a relatively fixed amount across all stages of training, compared to other inputs whose strength increases as animals gain experience.…”
Section: Discussionsupporting
confidence: 92%
“…The DLS is innervated by glutamatergic afferents from sensorimotor cortical areas (Hintiryan et al, 2016; McGeorge and Faull, 1989; Pennartz et al, 2009). The experience-dependent increase in MSN activity which was observed here, and in other studies (Barnes et al, 2005; Jin and Costa, 2010; Jog et al, 1999; Kimchi et al, 2009; Miyachi et al, 2002; Thorn et al, 2010; Yin et al, 2009), is consistent with an enhancement of corticostriatal coupling that accompanies some forms of learning (Koralek et al, 2013; O’Hare et al, 2016; Xiong et al, 2015). Thus, our results suggest that PV interneurons regulate MSN firing rate by a relatively fixed amount across all stages of training, compared to other inputs whose strength increases as animals gain experience.…”
Section: Discussionsupporting
confidence: 92%
“…To elucidate how the various consequences of elevated striatal mGluR5 signaling ultimately integrate within the striatal microcircuit to affect SPN firing, we used an approach we recently established that measures striatal output while preserving the influence of local circuit features (28). With the use of multiphoton laser vector-line scan microscopy of the calcium indicator dye, Fura-2, to visualize APs, we evoked SPN Firing by electrical stimulation of excitatory afferents (28) (Figure 2A–C).…”
Section: Resultsmentioning
confidence: 99%
“…(28). Briefly, acute parasagittal (300 µm) slices, corresponding to tissue approximately 300–900 µm medial to the first visible lateral aspect of dorsal striatum, were bulk loaded with the calcium indicator dye, Fura-2 AM (F-1221; Thermo Fisher Scientific, Waltham, MA) (Supplement).…”
Section: Methodsmentioning
confidence: 99%
“…Here we showed that modulation of the relative weights of the BG pathways could effectively modulate the SSRT, which provides a possible source for individual difference of the SSRT. Recently, goal directed or habitual behavior in rodents was associated with latency changes for the activation of direct and indirect pathways striatal neurons (O’Hare et al, 2016). It has been found that in goal directed response the indirect pathway striatal neurons showed a shorter latency than the direct pathway neurons.…”
Section: Discussionmentioning
confidence: 99%